Resolving the twin human and environmental health hazards of a plant-based diet. (November 2020) - Wyckhuys, Kris A.G.; Aebi, Alexandre; Bijleveld van Lexmond, Maarten F.I.J.; Bojaca, Carlos R.; Bonmatin, Jean-Marc; Furlan, Lorenzo; Guerrero, Jairo A.; Mai, Trinh V.; Pham, Hoi V.; Sanchez-Bayo, Francisco; Ikenaka, Yoshinori
Highlights: Fruits and vegetables constitute core constituents of 'planetary health' diets. In alleged healthful foods, pesticide residues are omnipresent – often surpassing MRL. We systematically map non-chemical alternatives per compound, commodity and country. Food producers possess myriad safe, practicable and effective non-chemical alternatives. Our work facilitates transitions towards ecologically-based farming tactics. Abstract: Food can be health-giving. A global transition towards plant-based diets may equally help curb carbon emissions, slow land-system change and conserve finite resources. Yet, projected benefits of such 'planetary health' diets imperfectly capture the environmental or societal health outcomes tied to food production. Here, we examine pesticide-related hazards of fruit and vegetable consumption, and list proven management alternatives per commodity, geography and chemical compound. Across countries, pesticide use in these alleged healthful foods is extensive with up to 97% food items containing residues and up to 42% posing dietary risks to consumers. Multiple residues are present in 70–92% of US- and China-grown stone fruit while 58% US cauliflower is tainted with neonicotinoid insecticides. Science-based alternatives and decision-support frameworks can help food producers reduce risks and potential harm by deliberately abstaining from pesticide use. As such, opportunities abound to advance 'win-win' diets that simultaneously nurture human health and conserve global biodiversity.